2013
DOI: 10.1371/journal.ppat.1003450
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immunomodulators from Hard Ticks Selectively Reprogramme Human Dendritic Cell Responses

Abstract: Hard ticks subvert the immune responses of their vertebrate hosts in order to feed for much longer periods than other blood-feeding ectoparasites; this may be one reason why they transmit perhaps the greatest diversity of pathogens of any arthropod vector. Tick-induced immunomodulation is mediated by salivary components, some of which neutralise elements of innate immunity or inhibit the development of adaptive immunity. As dendritic cells (DC) trigger and help to regulate adaptive immunity, they are an ideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 94 publications
(97 reference statements)
4
77
0
1
Order By: Relevance
“…Similar to previous studies -which found male-specific expression for HBPM (Paesen et al, 1999) and IGBP-M (Wang and Nuttall, 1995) genes and female-specific expression for HBP1, HBP2 (Paesen et al, 1999), Kunitz/BPTI-like protein, Ra-KLP (Paesen et al, 2009) and Japanin (Preston et al, 2013) genes -we found malespecific expression for HBPM and IGBP-Ms and female-specific expression for HBP1, HBP2, Ra-KLP and Japanin in our transcriptome. Expression profiling corroborated the publically available knowledge of R. appendiculatus genes.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to previous studies -which found male-specific expression for HBPM (Paesen et al, 1999) and IGBP-M (Wang and Nuttall, 1995) genes and female-specific expression for HBP1, HBP2 (Paesen et al, 1999), Kunitz/BPTI-like protein, Ra-KLP (Paesen et al, 2009) and Japanin (Preston et al, 2013) genes -we found malespecific expression for HBPM and IGBP-Ms and female-specific expression for HBP1, HBP2, Ra-KLP and Japanin in our transcriptome. Expression profiling corroborated the publically available knowledge of R. appendiculatus genes.…”
Section: Discussionsupporting
confidence: 92%
“…This was similar to what was shown for Japanin (Preston et al, 2013). The conserved cysteine residues and the tick Lipocalin motive, previously characterised in Japanin, were also observed in Rapp_Mc9023.…”
Section: Appendiculatussupporting
confidence: 88%
See 3 more Smart Citations